Comics as Media for Teaching Writing at the 7th Grade of SMP Negeri 5 Mrebet, Purbalingga - Anggun Fifi Mualifah; Irra Wahidiyati (Jurnal Vokasia, 2025)
This study explores the implementation of comics as a medium for teaching writing at the 7th grade of SMP Negeri 5 Mrebet, Purbalingga. The research employs a qualitative approach involving observation, interviews, and documentation. The subjects include one English teacher and three students who participated in comic-based writing lessons. The teacher implemented three stages of learning: exploration, elaboration, and confirmation. Comics were used to enhance students’ engagement and creativity in writing, particularly in creating dialogues and introductory expressions. The study found that while comics are effective in supporting writing instruction, several challenges arose, such as students’ difficulty in constructing coherent narratives, balancing text with visuals, and teachers’ limited visual literacy. Despite these challenges, comics served as a beneficial medium to promote student motivation and provide teachers with deeper insight into students’ learning obstacles.